Demographic change as a driver for tourism automation. Issue 3 (25th March 2020) - Webster, Craig; Ivanov, Stanislav
Abstract : Purpose: The purpose of this paper is to discuss how demographic changes in developed countries will continue to drive the tourism and hospitality industries to adopt automation in business operations. Design/methodology/approach: The approach is an analysis of the trends in human reproduction in the developed countries and a discussion of their implications for the travel, tourism and hospitality industries. Findings: There are three major solutions to the demographic problem faced in developed countries and the replacement of human labour with automation is the most practical, immediate and has the fewest risks and negative externalities. Practical implications: Industry has to adapt to the new demographic reality and embrace automation of services, educate their customers and have policies to deal with the resistance expected by labour. Social implications: Society can expect that many of the tasks they commonly expect humans to be involved in will be done by machines and artificial intelligence in the near future, if demographic trends continue and massive immigration into developed countries is not a continuing phenomenon. Originality/value: This links the relationship between demographic trends to the use of automation in the travel, tourism and hospitality industries.